DEVELOPMENT OF GEOGRAPHIC LITERACY BASED MODEL OF SOCIAL STUDIES LEARNING IN BUILDING STUDENTS’ ECO-FRIENDLY CHARACTER - Jakiatin Nisa; Enok Maryani; Epon Ningrum (Jurnal Sosioteknologi, 2020)
This study is derived from the fact that the eco-friendly character has still not been widely performed and the students’ geoliteracy has not been highly developed in social studies learning (IPS) in junior high schools in Bandung. This study is aimed at producing a social studies learning model which is expected to be an effort to build eco-friendly character, namely the Geographic Literacy Based Model in Building Eco-Friendly Character (BLG-KPL Model). The method used in this study is Research & Development (R&D). The study consists of preliminary session including the identification of needs (needs assessment), model development that includes some expert judgment, limited and extensive trials, and effectiveness test on the influence and the effect size. This research article will only describe the stage of developing the model with the assumption that the preliminary session has passed through extensive testing. The subjects of the study are teachers and the students in several junior high schools in Bandung. The data analysis of the model development consists of the feasibility test from the expert by conducting several revisions of the limited and extensive trials process. The results of the research in the model development stage produced 5 syntaxes with 4 revised changes based on limited and extensive trials. The first revision experienced a significant change from 6 syntaxes to 5 syntaxes. In the second and third revision, the main content was improved in reference to the limited trials results because it was not still significant to building eco-friendly character and the fourth revision was a recommendation from an extensive trial which shows that it had already been significant in building the character, with some technical revisions in the operational stage of applying the model. Penelitian ini berangkat dari rendahnya karakter peduli lingkungan dan kurang dikembangkannya literasi geografi peserta didik dalam pembelajaran Ilmu Pengetahuan Sosial (IPS) di SMPN Kota Bandung. Penelitian ini bertujuan untuk melahirkan model pembelajaran IPS yang diharapkan bisa menjadi upaya dalam menumbuhkan karakter peduli lingkungan, yaitu Model Berbasis Literasi Geografi - Karakter Peduli Lingkungan yang kemudian disingkat Model BLG-KPL. Metode yang digunakan dalam penelitian ini adalah Research & Developmnet (R&D). Tahapan penelitian terdiri dari tahap pendahuluan, meliputi identifikasi kebutuhan (needs assessment), tahap pengembangan model, meliputi telaah ahli (expert), uji terbatas dan uji luas dan tahap pengujian efektivitas pengaruh dan besaran efek model. Pada artikel penelitian ini hanya akan memaparkan tahap pengembangan modelnya saja dengan asumsi sudah dilalui tahap pendahuluan sampai pengujian luas. Subjek penelitian adalah guru dan peserta didik di beberapa SMPN Kota Bandung. Analisis data tahap pengembangan model terdiri dari uji kelayakan dari ahli (expert) dengan dilakukan beberapa kali revisi dari proses pengujian terbatas dan luas. Hasil penelitian tahap pengembangan model menghasilkan 5 sintaks dengan perubahan revisi sebanyak 4 kali berdasar uji lapangan terbatas dan luas. Pada revisi pertama mengalami perubahan signifikan dari 6 sintaks menjadi 5 sintaks. Pada revisi kedua mengalami perbaikan substansi berdasar hasil uji terbatas karena masih belum menujukkan signifikan menumbuhkan karakter peduli lingkungan dan revisi keempat merupakan rekomendasi dari uji luas yang sudah menunjukkan signifikan menumbuhkan karakter peduli lingkungan dengan revisi teknis dalam tahap operasional penerapan model.